HPV prevalence among women from Appalachia: results from the CARE project. - Paul L Reiter (PLoS ONE, 2013)
Cervical cancer incidence and mortality rates are high among women from Appalachia, yet data do not exist on human papillomavirus (HPV) prevalence among these women. We examined the prevalence of genital HPV among Appalachian women and identified correlates of HPV detection.We report data from a case-control study conducted between January 2006 and December 2008 as part of the Community Awareness, Resources, and Education (CARE) Project. We examined HPV prevalence among 1116 women (278 women with abnormal Pap tests at study entry [cases], 838 women with normal Pap tests [controls]) from Appalachian Ohio. Analyses used multivariable logistic regression to identify correlates of HPV detection.The prevalence of HPV was 43.1% for any HPV type, 33.5% for high-risk HPV types, 23.4% for low-risk HPV types, and 12.5% for vaccine-preventable HPV types. Detection of any HPV type was more common among women who were ages 18-26 (OR = 2.09, 95% CI: 1.26-3.50), current smokers (OR = 1.86, 95% CI: 1.26-2.73), had at least five male sexual partners during their lifetime (OR = 2.28, 95% CI: 1.56-3.33), or had multiple male sexual partners during the last year (OR = 1.98, 95% CI: 1.25-3.14). Similar correlates were identified for detection of a high-risk HPV type.HPV was prevalent among Appalachian women, with many women having a high-risk HPV type detected. Results may help explain the high cervical cancer rates observed among Appalachian women and can help inform future cervical cancer prevention efforts in this geographic region.